Low wages aren't a growing problem - David Abraham; Simcha Barkai (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2022)
Statements by high-profile political figures and supporting academic research have led to a common perception of worsening job prospects for low-wage workers in the US. In this paper, we show that since the early 1980s there has been a decline in the share of workers earning low wages. This holds across sub-populations and across thresholds for determining what constitutes a low wage. Much of the decline occurs over two periods: the late 1990s and the late 2010s. The decline is greater and steadier for women than for men. We further show that the worker-level persistence of low wages has not increased, and has likely decreased, over time.
Keywords: 330; Niedriglohn; Arbeitskräfte; Soziale Mobilität; USA